2016
DOI: 10.1007/s10067-016-3306-x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokine levels, disease activity, and function of patients with rheumatoid arthritis treated with combined conventional disease-modifying antirheumatic drugs or biologics

Abstract: The objective of this study was to compare the effects of treatment by combined conventional disease-modifying antirheumatic drugs (cDMARDs) or biologics on cytokines, disease activity, and function in rheumatoid arthritis (RA). Sera from a cohort of 81 patients with long-standing RA treated with combined cDMARDs or biologics were measured for 12 cytokines. Comparisons of serum cytokine concentrations with treatment types (combination 2, 3 cDMARDs or biologics), serologic status (positivity for RF and anti-cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…It is overexpressed in many tumors and cancer cell lines, and promotes tumor growth, angiogenesis, and metastasis in a variety of human cancers [161]. It is also elevated in the serum and synovial fluid of RA patients [162]. Production of IL-8 by breast cancer cells increases osteoclast formation and may contribute to bone metastasis [163].…”
Section: Il-8mentioning
confidence: 99%
“…It is overexpressed in many tumors and cancer cell lines, and promotes tumor growth, angiogenesis, and metastasis in a variety of human cancers [161]. It is also elevated in the serum and synovial fluid of RA patients [162]. Production of IL-8 by breast cancer cells increases osteoclast formation and may contribute to bone metastasis [163].…”
Section: Il-8mentioning
confidence: 99%
“…However, several clinical studies showed no significant differences concerning therapeutic efficacies between the two types of medications in treating RA patients (Osiri et al. 2016 ). cDMARDs are inexpensive and efficacious, and therefore are commonly used as the first-line drugs in clinical practice until now.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, other subjects also used a combination of DMARD therapy. The study of Osiri et al [24], which also used a combination of 2 DMARD and 3 DMARD, showed low TNF-α level, 1.22 pg/mL and 1.44 pg/dL, respectively.…”
Section: Discussionmentioning
confidence: 97%